2021
DOI: 10.3390/nu13072318
|View full text |Cite
|
Sign up to set email alerts
|

Early Introduction of Food Allergens and Risk of Developing Food Allergy

Abstract: There is increasing evidence that early introduction of allergenic foods may decrease the risk of developing IgE-mediated food allergy. Patterns of food introduction before the 2015 publication of the Learning Early about Peanut Allergy (LEAP) trial are not well-studied, but are important as a baseline for evaluating subsequent changes in infant feeding practices and potentially food allergy. We performed a retrospective longitudinal study using data from a multicenter cohort of infants hospitalized with bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 50 publications
0
27
0
2
Order By: Relevance
“…Delayed introduction of the most common allergens by time of complementary food introduction for prevention of food allergy, including CMA, is strongly discouraged by EAACI, ASCIA, and AAAAI, as there is no evidences for its beneficial effect [ 81 , 83 , 84 ]. In fact, several studies have shown that early introduction of allergenic foods, such as peanuts [ 98 , 99 ], cow’s milk [ 100 , 101 ], or hen’s egg [ 99 ], can decrease the risk of developing food allergy against the particular allergens [ 102 ].…”
Section: Food Allergymentioning
confidence: 99%
“…Delayed introduction of the most common allergens by time of complementary food introduction for prevention of food allergy, including CMA, is strongly discouraged by EAACI, ASCIA, and AAAAI, as there is no evidences for its beneficial effect [ 81 , 83 , 84 ]. In fact, several studies have shown that early introduction of allergenic foods, such as peanuts [ 98 , 99 ], cow’s milk [ 100 , 101 ], or hen’s egg [ 99 ], can decrease the risk of developing food allergy against the particular allergens [ 102 ].…”
Section: Food Allergymentioning
confidence: 99%
“…Хоча з'являються нові докази того, що оптимізація догляду за екзематозною шкірою для підтримки здорового шкірного бар'єра і, отже, запобігання харчовій сенсибілізації (ХС), ймовірно, відіграє важливу роль у профілактиці харчової алергії [6, 7], підхід, підкріплений найбільш переконливими даними, стосується раннього введення в раціон алергенних продуктів, особливо яєць та арахісу [8][9][10].…”
Section: значення харчової алергії при атопічному дерматиті в дітейunclassified
“…This led to the modern recommendation by medical experts to expose children to common allergenic foods early in life. 4 It is now thought that sensitization to food allergens may actually occur primarily due to dermal and/or inhalation exposure to food dust, whereas exposure to these same allergens in the gut favors tolerization against allergy (dual allergen exposure hypothesis). 5 , 6 …”
Section: Pediatric Recommendations On Exposure To Foodsmentioning
confidence: 99%